Reversing the Occurrence of Double Road Accidents: A Tour Bus Collision with a Semi – Trailer Truck in Nakhon Si Thammarat Province - Kanchanapen, Ekkalak; Chuayjan, Witsarut; Kaewdmai, Roihathai; Kaewdee, Chatchai; Sudsomboon, Weerayute; Pansrinual, Weeraphol (Academic Journal of Industrial Technology Innovation, 2023)
This paper aims to analyze the causes of double road accidents and suggest the preventions by considering three factors: road factor, vehicle factor and human factor. There were two processes in this research: data collection and data analysis. In the data collection, the researcher participated with The Office of Disease Prevention and Control 11 Nakhon Si Thammarat Province to collect the data by using Theodolite, surveyor’s wheel, and surveyor’s tape. After that, the results of data collection were used to simulate the road accidents by using CAD ZONE software. In the data analysis, the researcher used data from survey to find a model of collision and analyzed the vehicle speed before and after collisions by applying acceleration physics equation and CAD Zone software. The results showed that the causes of accidents were human and driving speed. The pre-collision speed of the semi-trailer truck was equal to 104 km/hour which led to severe damage when the car breaks down and hit a large tree and the accident area prevention management system was not strictly controlled. During helping the victims of semi-trailer trucks, the bus drove 110 km/hour hit the back of the semi-truck that extended from the shoulder line about 1 m. Therefore, the recommendations to prevent double road accident were to focus on prevention area and control the speed limit according to the laws.